Risk Factors of Laryngeal Carcinoma in Otorhinolaryngology-Head and Neck Division of Dr. Hasan Sadikin Hospital Bandung - Sarah A Putri; Yussy A Dewi; Birgitta M Dewayani (Journal of Medicine and Health, 2018)
Laryngeal carcinoma is a squamous cell malignancy of larynx epithelial with the Indonesian incidence of 2.0 per 100,000 men and 0.2 per 100,000 women. The risk factors of laryngeal carcinoma include age, sex, family history, smoking habit, alcohol drink, and gastroesophangeal reflux disease (GERD)/ laryngopharyngeal reflux (LPR). This study aimed to know some risk factors for laryngeal carcinoma mentioned in Dr. Hasan Sadikin Hospital, Bandung. Hospital-based unmatched case control study was selected as the methods, involving 80 patients in Oncology Clinic of Otorhinolaryngology-Head and Neck Surgery Department, Dr. Hasan Sadikin General Hospital. The medical records of the carcinoma larynx patients was taken as a study instrument. The results were age percentage of 50-79 years old in the case group is 82.5% therefore, it increase the risk of having laryngeal carcinoma by 7.29 times. Male respondents dominate in the case group (90%) with OR =6.00. Respondents with GERD in the case group is 45%, increasing the risk 15.54 times and these results was significant (p<0.005). Other analyzed variables, such as family history, smoking history, and alcohol consumption is not significant statistically (p>0.005). This study shows the results of age, sex, and GERD/LPR are corresponding with the results with previous studies. Otherwise, the results of smoking, alcohol, and family history are not. Therefore, old age, male sex, and GERD increase the risk of having laryngeal carcinoma.